Acute kidney disease: an overview of the epidemiology, pathophysiology, and management - Chin-Wei Kung; Yu-Hsiang Chou (The Korean Society of Nephrology, 2023)
Acute kidney injury (AKI) increases the risk of chronic kidney disease (CKD), and AKI and CKD are seen as interconnected syndromes. Acute kidney disease (AKD) is defined as subacute damage and/or loss of kidney function occurring 7 to 90 days after AKI, during which period key interventions may be initiated to hinder the development of CKD. While AKD is usually under-recognized, it is associated with high morbidity and mortality globally. This review article aims to summarize the current knowledge concerning the epidemiology, pathophysiology, and management of AKD with the aim to develop monitoring strategies and therapeutic agents of AKD. Generally, AKD tends to occur more frequently in the elderly and those with chronic diseases, such as hypertension, diabetes mellitus, and metabolic syndrome. In addition, the severity, duration, and frequency of AKI are independent risk factors for AKD. Investigations of several mechanisms of AKD, such as renal tubular epithelium cell-cycle arrest, epigenetic change, chronic inflammation, mitochondria dysfunction, failed regeneration of tubular cells, metabolic reprogramming, and renin-angiotensin system (RAS) activation, have identified additional potential pharmacotherapy targets. Management of AKD includes prevention of repeated AKI, early and regular follow-up by a nephrologist, resumption and adjustment of essential medication, optimization of blood pressure control and nutrition management, and development of new pharmaceutical agents including RAS inhibitors. Finally, we outline a care bundle for AKD patients based on important lessons learned from studies and registries and identify the need for clinical trials of RAS inhibitors or other novel agents to impede ensuing CKD development.